Sri Lanka : An Ideological Power Struggle - Suryanarayana, Pisupati Sadasiva (2019)
The ideological moorings of leaders in Sri Lanka, as they struggle for power, are as important as the strategic stakes of China and India in the Indian Ocean island state.